Visual Learning-Style-Based Activities in Improving the Reading Comprehension Skills of Second-Year English Major Students - Gallardo, Jodilly; Dela Cruz, Nicole; Opinga, Gloede; Albino, Femia S. (Future Science / FSH-PH Publications, 2023)
This research paper aimed to investigate the effects of visual learning style-based activities on reading comprehension skills among 18 second-year English major students who are currently enrolled at the President Ramon Magsaysay State University-Castillejos Campus. The matching-only pretest-post-test research design, as a type of experimental design, was used to investigate the improvement of the respondents' reading comprehension skills after the integration of the intervention. The results show that the student’s reading comprehension level was mostly “Independent” or 38.89% (7 out of 18) during the administration of the pre-test and increased by 66.67% (12 out of 18) during the administration of the post-test. The mean score of the respondents shows that they are in the “Instructional” level (19.83 or 66.11%) on the pre-test result which was improved during the post-test result in the “Independent” level (24.17 or 80.57%) respectively. The pre-test and post-test results on the reading comprehension of the respondents before and after the application of the visual learning style-based intervention show a significant correlation between the mean score (t=4.32, p=2.11) which is <0.05 alpha level, thus, the rejection of the null-hypothesis. Moreover, instructors may also allow their respective students to develop their reading comprehension skills beyond the given activities by supplying learning activities tailored to their needs, interests, and learning styles.